Wearable temperature sensor based on graphene nanowalls1. Issue 32 (10th April 2015) - Yang, Jun; Wei, Dapeng; Tang, Linlong; Song, Xuefen; Luo, Wei; Chu, Jin; Gao, Tianpeng; Shi, Haofei; Du, Chunlei
<x xml:space="preserve">Abstract</x> This work reports an ultrasensitive wearable temperature sensor based on GNWs/PDMS for personalized healthcare and human–machine interface systems.